A crustal LVZ in Iceland revealed by ambient noise multimodal surface wave tomography - Zhang, Sen; Zhang, Gongheng; Feng, Xuping; Li, Zhengbo; Pan, Lei; Wang, Jiannan; Chen, Xiaofei (Frontiers in Earth Science, 2022)
The crustal low-velocity zone (LVZ), an important anomaly found in some regional structures of Iceland, is still absent in Icelandic average velocity structure due to limitations of tomography methods. By stations from the HOTSPOT experiment and other supplemental stations throughout Iceland, we apply the frequency-Bessel transform method (F-J method) to extract the first two mode dispersion curves from ambient noise data. We obtain an average S-wave velocity (Vs) model of Iceland down to 120 km depth, where two LVZs at depths of 12 to 22 km and below 55 km are found. The shallow LVZ, whose rationalities are justified using theoretical dispersion curves of certain models to recover themselves, may improve the understanding of the Icelandic average crust. Furthermore, our model shows better representativeness by comparing travel time residuals of the primary wave between observed and synthetic data predicted using different average velocity models. Based on the variations of Vs gradient, the Icelandic crust with an average thickness of 32 km is divided into upper crust (0–10 km), middle crust (10–22 km), and lower crust (22–32 km). The asthenosphere starts from the deeper LVZ at 55 km depth potentially indicating the relatively concentrated melt in this depth range. In this study, the crustal LVZs are revealed both in a volcanic active zone and a non-volcanic zone, which may also suggest the LVZ in the average model has complex origins more than the high temperature beneath the central volcanoes. The prevalent thick-cold crustal model of Iceland, considered to rule out the existence of a broad region of partial melt in the crust, also strengthens the possibility of diverse origins. The variations in petrology may also contribute to the crustal LVZ in the average model.